Analisis Potensi dan Kualitas Madu Hutan Apis dorsata pada Hutan Mangrove di Kabupaten Ogan Komering Ilir Provinsi Sumatera Selatan Indonesia - Rosianty, Yuli; Rahmad, Beni; Pradita, Sonya Rahma; Harefa, Ribka (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyze the production potential and quality of forest honey (Apis dorsata) in the Mangrove Forest Reserve of Sungai Lumpur, Ogan Komering Ilir Regency, South Sumatra. The research was conducted through field surveys and laboratory analyses. The parameters observed included honey production potential, moisture content, ash content, reducing sugars, sucrose, acidity, and heavy metal concentrations. The results showed that forest honey production significantly increased during the harvest season, contributing to a 30–35% higher income compared to normal conditions. Laboratory tests indicated that the honey had a moisture content of 26.4% (exceeding the SNI 8664:2018 standard), ash content of 0.18% (within standard), reducing sugars of 64.4% (slightly below the minimum 65%), sucrose of 0% (within standard), acidity of 20.3 ml NaOH/kg (within standard), and heavy metal levels (Pb, Cd, Hg, As, Sn) below permissible limits. Therefore, forest honey from this mangrove reserve has considerable economic potential for local communities, but improvements in harvesting, processing, and storage techniques are required to ensure compliance with quality standards.